Neck circumference as a screening measure of overweight/obesity among Indian adults - Mondal, Nitish; Sen, Jaydip; Bose, Kaushik; Timungpi, Ruplin; Kathar, Moniram; Hanse, Sarlongki (Anthropological Review, 2016)
Neck circumference (NC) is an anthropometric measurement of differentiating body fat distributions and a marker of upper subcutaneous adiposity. The present study highlights the association and importance of NC as a suitable proxy screening measure of overweight/obesity as compared to the conventional anthropometric variables used among Indian adults. The present community based cross-sectional study was undertaken among 1169 Karbi adults (males: 625; females: 544) residing in Karbi Anglong district of Assam, Northeast India, who were selected through a multistage stratified random sampling method. Height, weight, waist circumference (WC), hip circumference (HC) and NC were recorded using standard procedures. The body mass index (BMI) was calculated and prevalence of overweight/obesity was assessed using standard cut-offs. The prevalence of obesity using BMI (≥25.00 kg m-2) was 15.52% and 15.26% among males and females, respectively (p≥0.05).The prevalence of obesity using NC was observed to be significantly higher among males (48.80%) than females (19.12%) (p<0.01). The binary logistic regression analysis showed that NC predicted obesity over the conventional anthropometric variables with reasonable accuracy (p<0.01). The ROC-AUC analysis showed a relatively greater significant association between BMI, WC and HC and NC for obesity (p<0.01). Thus, NC appears to be a potentially simple, easyto- use screening measure for predicting obesity among adults. Further studies are required to validate its use for screening of obesity among other ethnic populations in India.